LITERATURE REVIEW KAJIAN ETIS PENGHENTIAN TERAPI MEDIS DALAM PERSPEKTIF PRINSIP MORAL BIOETIKA - Ni Putu Alya Magfira Cantika Putri; Meivy Isnoviana (PT. Saha Kreasi Indonesia, 2025)
The controversy surrounding end-of-life medical practices such as euthanasia, Do Not Resuscitate (DNR), and the withdrawal or withholding of life-sustaining treatment remains a complex bioethical issue in Indonesia. The debate lies between the right to life as an absolute human right and the patient’s autonomy to determine their own fate, particularly in terminal cases where medical treatment is considered futile. This study aims to analyze the legal standing and ethical implications of withdrawing medical treatment from the perspectives of Indonesian positive law, the Indonesian Medical Code of Ethics (KODEKI), and Islamic law. This research employs a literature review method with a normative juridical approach through a review of legal instruments such as the Ministry of Health Regulation No. 37 of 2014, KODEKI, bioethical literature, and Islamic legal sources. The analysis was conducted descriptively and deductively to examine the consistency between legal norms and medical ethical principles. The findings show that active euthanasia remains prohibited by both law and medical ethics as it contradicts the principle of preserving life (sanctity of life). However, the withdrawal or withholding of life-sustaining treatment that no longer provides medical benefit is permissible under limited conditions, based on clear clinical judgment, family consent, and respect for patient dignity. In conclusion, there is a need for more specific regulatory and ethical harmonization to provide legal protection for healthcare professionals, uphold patient autonomy, and ensure the implementation of the four bioethical principles (autonomy, beneficence, non-maleficence, and justice) in medical treatment withdrawal practices in Indonesia.